Essence of diplomacy - Jönsson, Christer 1944-; Hall, Martin 1967- (Studies in diplomacy and international relations, 2005)
In their effort at making international relations (IR) theory relevant to diplomacy, and diplomacy relevant to IR theory, the authors identify three essential dimensions of diplomacy: communication, representation and the reproduction of international society